ASPEK, ADVERBIA WAKTU, DAN KALA DALAM BAHASA INGGRIS DAN BAHASA INDONESIA (Aspect, Adverb of Time, and Tenses in English and Indonesian) - Mansur Akil (Balai Bahasa Sulawesi Selatan, 2009)
English-Indonesian translators often find difficulties in translating English verb. This is due to their lack of understanding of the concept of aspect, adverb of time in both English and Indonesian, and tenses in English. This articles is trying to address this problem in term oh their syntactic behavior, since the translators very often make mistakes in this way. Although English and Indonesian are different in those cases, the concept of aspect and tenses in English still can be conveyed into Indonesian. The simple tenses can be conveyed closely to their natural senses, but the complex tenses comprising double aspects or more like perfective-durative are little bit difficult to find the close translation. Certain nuances especially those related to culture are even impossible to convey, for naturally a certain language can only exactly express the meaning of its own culture. Anyway, these difficulties can be solved by making some paraphrases having the same deep structure as the message to render. While to translate tenses and their aspects can be done by using particleslike:masih,sedang,sudah/telahandadverbsoftimesuchaskemarin,tadi,besok,lusaandminggudepan.